Understanding employee responses to the covid-19 pandemic: a sensemaking humanitarian solidarity perspective - Santoso, Nobertus Ribut (Faculty of Communications Science, Dr. Soetomo University, 2022)
Most organisations in the world are facing great challenges due to the COVID-19 pandemic. They must struggle to sustain their business operation. Through a qualitative study, this study investigates how employees make sense of the COVID-19 pandemic, driving them to take actions of humanitarian solidarity to keep their organisation sustainable. Through a semi-structured interview, eight employees from various organisations were interviewed. The data were coded and analysed inductively. The findings reveal that employees’ sensemaking towards the pandemic encourages them to take actions on humanitarian solidarity to their organisation by working together, helping and supporting each other, promoting a feeling of unity, and being productive, motivated, and enthusiastic to maintain the sustainability of the organisation. Moreover, internalization of organic organisational values to employees promotes their humanitarian solidarity behaviours due to the pandemic by collecting information, processing information, reducing ambiguous and clearing complex information, building simple information, and supporting organisation.